2020
DOI: 10.1177/1099800420923397
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Noise in the Intensive Care Unit on the Oxidative Stress Response in Rats

Abstract: Objective: The objective of this study was to determine the effect of noise in the intensive care unit (ICU) on oxidative stress in a rat model. Method: This study had both a descriptive and a randomized controlled experimental stage. In the descriptive stage, to create a laboratory model of noise in the ICU, the noise level was measured for 24 hr on a randomly selected day in a surgical ICU, and voice recording was performed using a sound recording device. In the experimental stage, 30 male Wistar albino rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…These noise-induced changes are considered as biomarkers that can influence inflammatory and oxidative stress and can predict future diverse diseases, including cardiovascular diseases [20]. Recently, an animal study reported increased oxidative stress in rats that had been exposed to noise mimicking that in the ICU environment [21]. However, the pathogenetic mechanism underlying the way in which noise exposure is related to cognitive impairment has not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…These noise-induced changes are considered as biomarkers that can influence inflammatory and oxidative stress and can predict future diverse diseases, including cardiovascular diseases [20]. Recently, an animal study reported increased oxidative stress in rats that had been exposed to noise mimicking that in the ICU environment [21]. However, the pathogenetic mechanism underlying the way in which noise exposure is related to cognitive impairment has not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%